Finite element simulation of delamination process in composite materials - Sabău Emilia; Vilău Cristian; Bere Paul; Popescu Adrian (MATEC Web of Conferences, 2019)
The delamination phenomenon is undesirable and constitutes a major problem. In this paper, a study of delamination for composite materials reinforced with unidirectional glass fibers in polyester matrix is analyzed. The composite plates were made using two manufacturing technologies, hand lay-up and compression hand lay-up process. The study found out the maximum value of the force where delamination occurs and the specific delamination resistance. Also, it’s done a finite element simulation of delamination process at polymeric composite materials under transverse loads. The propagation model ofdelamination was implemented in finite element ANSYS software. There are presented the used materials for samples, the manufacturing process, laboratory equipment and the experimental results.